Increased Drp1-Mediated Mitochondrial Fission Promotes Proliferation and Collagen Production by Right Ventricular Fibroblasts in Experimental Pulmonary Arterial Hypertension - Tian, Lian; Potus, Francois; Wu, Danchen; Dasgupta, Asish; Chen, Kuang-Hueih; Mewburn, Jeffrey; Lima, Patricia; Archer, Stephen L. (Frontiers in Physiology, 2018)
Introduction: Right ventricular (RV) fibrosis contributes to RV failure in pulmonary arterial hypertension (PAH). The mechanisms underlying RV fibrosis in PAH and the role of RV fibroblasts (RVfib) are unknown. Activation of the mitochondrial fission mediator dynamin-related protein 1 (Drp1) contributes to dysfunction of RV myocytes in PAH through interaction with its binding partner, fission protein 1 (Fis1). However, the role of mitochondrial fission in RVfib and RV fibrosis in PAH is unknown. Objective: We hypothesize that mitochondrial fission is increased in RVfib of rats with monocrotaline (MCT)-induced PAH. We evaluated the contribution of Drp1 and Drp1-Fis1 interaction to RVfib proliferation and collagen production in culture and to RV fibrosis in vivo. Methods: Vimentin (+) RVfib were enzymatically isolated and cultured from the RVs of male Sprague Dawley rats that received MCT (60 mg/kg) or saline. Mitochondrial morphology, proliferation, collagen production, and expression of Drp1, Drp1 binding partners and mitochondrial fusion mediators were measured. The Drp1 inhibitor mitochondrial division inhibitor 1 (Mdivi-1), P110, a competitive peptide inhibitor of Drp1-Fis1 interaction, and siRNA targeting Drp1 were assessed. Subsequently, prevention and regression studies tested the antifibrotic effects of P110 (0.5 mg/kg) in vivo. At week-4 post MCT, echocardiography and right heart catheterization were performed. The RV was stained for collagen. Results: Mitochondrial fragmentation, proliferation rates and collagen production were increased in MCT-RVfib versus control-RVfib. MCT-RVfib had increased expression of activated Drp1 protein and a trend to decreased mitofusin-2 expression. Mdivi-1 and P110 inhibited mitochondrial fission, proliferation and collagen III expression in MCT-RVfib. However, P110 was only effective at high doses (1 mM). siDrp1 also reduced fission in MCT-RVfib. Despite promising results in cell therapy, in vivo therapy with P110 failed to prevent or regress RV fibrosis in MCT rats, perhaps due to failure to achieve adequate P110 levels or to the greater importance of interaction of Drp1 with other binding partners. Conclusions: PAH RVfib have increased Drp1-mediated mitochondrial fission. Inhibiting Drp1 prevents mitochondrial fission and reduces RVfib proliferation and collagen production. This is the first description of disordered mitochondrial dynamics in RVfib and suggests that Drp1 is a potential new antifibrotic target.